Chapter 6. Must a Patient Be a Person to Be a Patient?: Or, My Uncle Charlie Is Not Much of a Person But He Is Still My Uncle Charlie - Hauerwas, Stanley (Journal of religion, disability & health, 2005)
Hauerwas urges us to move away from the concept of the ‘person.’ He suggests that the concept of ‘person’ is inadequate but probably also misleading and even dangerous. As a regulative notion to define the relation between doctor and patient the concept of person not only does violence to our language but fails to provide sufficient moral content to the practice of medicine and health care. He argues that the concept of ‘person’ not only suffers from abstraction by taking us out of the concrete social structure (community) and historical narrative (story) in which humans live, but can actually distort the practices, institutions and notions which underlay how we have learned morally to display our lives. While the idea of the ‘person’ can act as a moral restraint for some of the excesses of medical technology, its parameters often exclude, rather than include, people with disabilities. Hauerwas argues that in the absence of a shared moral vision for medical practices the concept of the person is questionable and perhaps even dangerous. He calls Christians and Jews to re-think the moral basis of medicine and to practice a form of medicine which is faithful to their traditions.